2019
DOI: 10.1016/j.bja.2018.08.025
|View full text |Cite
|
Sign up to set email alerts
|

ROR2 modulates neuropathic pain via phosphorylation of NMDA receptor subunit GluN2B in rats

Abstract: Background: Neuropathic pain, a type of chronic pain as a result of direct central or peripheral nerve damage, is associated with significant quality of life and functional impairment. Its underlying mechanisms remain unclear. We investigated whether ROR2, a member of the receptor tyrosine kinase-like orphan receptor (ROR) family, participates in modulation of neuropathic pain. Methods: Thermal hyperalgesia and mechanical allodynia were measured using radiant heat and von Frey filament testing. Immunofluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 44 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Technical limitations hinder us from establishing this link. Ryk and Ror2 are expressed widely in spinal neurons in chronic pain states (Liu et al, 2015;Zhou et al, 2019), and are particularly broadly found across the neuropil, rendering it likely that these receptors are indeed expressed on neurons undergoing remodeling in chronic pain states. Our data on localization of these receptors to synaptic markers further render this likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical limitations hinder us from establishing this link. Ryk and Ror2 are expressed widely in spinal neurons in chronic pain states (Liu et al, 2015;Zhou et al, 2019), and are particularly broadly found across the neuropil, rendering it likely that these receptors are indeed expressed on neurons undergoing remodeling in chronic pain states. Our data on localization of these receptors to synaptic markers further render this likely.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt5a was also implicated in the pathogenesis of EAE-associated chronic pain via inducing the expression of the cytokines known mediators of neuroinflammation (Yuan et al, 2012). Wnt5a is known to bind preferentially the atypical receptors Ror2 and Ryk; interestingly, both receptors have been reported to play a role in neuropathic pain models (Liu et al, 2015;Yang et al, 2017;Zhu et al, 2018;Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, accumulated evidence shows that ROR2 is activated and upregulated after CCI, while inhibition of ROR2 reverses the nociceptive effect. 16 Therefore, we speculate that melatonin may exert painpromoting effects through activation of ROR instead of MT receptors, which needs further study.…”
Section: Mechanisms Of Action On Animal Models Melatonin Receptorsmentioning
confidence: 92%
“…[11][12][13] It has been suggested that melatonin regulates pain via membrane receptors, nuclear receptors, and simple diffusion. [14][15][16][17] Given these properties with few adverse side effects, melatonin has potential as a painkiller. The aim of this review is to discuss and analyze different lines of evidence for the effects of melatonin on pain modulation as well as to describe the cellular mechanisms of melatonin as a potential analgesic.…”
Section: Introductionmentioning
confidence: 99%
“…Following nerve injury, significant amounts of excitatory neurotransmitter glutamate are continuously released in the synaptic junctions of the spinal dorsal horn, activating the glutamate receptor (Glu-R), N -methyl- d -aspartate (NMDA) receptor (NMDAR), and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPA receptor, AMPAR). Receptors then transmit pain signals to sensory brain regions [ 88 , 89 , 90 ]. Studies in various animal models have confirmed that blocking NMDAR can relieve NP [ 91 ].…”
Section: Stem Cell Therapymentioning
confidence: 99%